Adsorption cooling cycles: Insights into carbon dioxide adsorption on activated carbons. (1st May 2016) - Fan, Wu; Chakraborty, Anutosh; Kayal, Sibnath
Abstract: We present an extensive study to measure CO2 uptakes on various AC (activated carbons) such as Maxsorb III, ACF-A20, BPL, Norit and honeycomb monolith for the temperatures ranging from 303 K to 363 K and pressures up to 10 MPa. These adsorbent samples were characterized using adsorption of nitrogen, XRD (X-ray diffraction), FTIR (Fourier transform infrared) and SEM (scanning electron micrography). The isosteric heat of adsorption ( Q st ) at low surface coverage is calculated form experimentally measured isotherm data. In this paper, the Q st at low surface coverage is calculated theoretically as a function of the collision diameter and the well depth potential of activated carbons – CO2 system. These results are compared with experimental data. Employing thermodynamic frameworks of adsorbent – adsorbate system and Q st formulation as a function of adsorbent pore widths, the COP (coefficient of performance) of adsorption cooler is calculated for various heat source and cooling load temperatures. It is found that the COP is influenced mainly by the pore sizes of solid adsorbents, and the adsorptive sites between the adsorbent-adsorbate systems. The present study confirms that the pore widths of activated carbons ranging from 7 to 15 Å allow us to obtain the best cooling performances. Highlights: Activated carbons are characterized using adsorption of nitrogen, XRD, FTIR and SEM. CO2 uptakes on various activated carbons. Heat of adsorption formulation as a function of pore width. COP is calculated as a function of pore width. Pore widths ranging from 7 to 15 Å exhibit the best cooling performances.